2020
DOI: 10.1590/1414-431x20209861
|View full text |Cite
|
Sign up to set email alerts
|

Enriched environment improves sevoflurane-induced cognitive impairment during late-pregnancy via hippocampal histone acetylation

Abstract: Fetal exposure to sevoflurane induces long-term cognitive impairment. Histone acetylation regulates the transcription of genes involved in memory formation. We investigated whether sevoflurane exposure during late-pregnancy induces neurocognitive impairment in offspring, and if this is related to histone acetylation dysfunction. We determined whether the effects could be reversed by an enriched environment (EE). Pregnant rats were exposed to 2.5% sevoflurane or control for 1, 3, or 6 h on gestational day 18 (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The present results showed that MSD decreased the protein expression levels of BDNF and TrkB in the elderly offspring, which further supports that decreased expression of BDNF and TrkB may be a potential cause of depression and cognitive impairment. A previous study showed that the downregulation of BDNF expression induced by maternal sevoflurane exposure was reversed by EE through increasing the level of histone acetylation ( Yu et al, 2020b ). Consistently, we found that EE reversed the MSD-induced downregulation of the BDNF/TrkB signaling pathway to improve depression and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The present results showed that MSD decreased the protein expression levels of BDNF and TrkB in the elderly offspring, which further supports that decreased expression of BDNF and TrkB may be a potential cause of depression and cognitive impairment. A previous study showed that the downregulation of BDNF expression induced by maternal sevoflurane exposure was reversed by EE through increasing the level of histone acetylation ( Yu et al, 2020b ). Consistently, we found that EE reversed the MSD-induced downregulation of the BDNF/TrkB signaling pathway to improve depression and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of an enriched environment (EE) was proposed by Hebb in 1947 and is a simple and effective method to improve cognitive deficits (Alwis and Rajan, 2014 ). EE is an experimental paradigm that allows mice to receive sensory, motor, and social stimulation by placing them in larger devices equipped with a variety of toys and running wheels (Yu et al, 2020 ; Zhang et al, 2021 ). EE has been found to affect cell survival, neurogenesis, synaptogenesis, and dendritic morphology in the hippocampus (Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sevoflurane is often used for anesthesia during pregnancy, and many studies have begun to preliminarily explore whether and how sevoflurane may have lasting harmful effects on the brains of gestationally exposed offspring. Multiple mechanisms are involved in neuronal damage to offspring, for example neuronal apoptosis [ 16 ], synaptic plasticity [ 17 ], and BDNF-related pathways [ 18 , 19 ]. Chai et al [ 20 ] reviewed the fundamentals of fetal toxicity related to gestational sevoflurane exposure and demonstrated that the pathology associated with fetal toxicity involves oxidative stress, neuroinflammation, neuronal apoptosis, and alteration of synaptic properties.…”
Section: Discussionmentioning
confidence: 99%